Moderating Effect of Business Environment on the Relationship Between Foreign Direct Investment and Local Firm’s Performance - Wanjere M. D.; Kinoti M.; Irai X. N.; Ogutu M. (European Scientific Journal, ESJ, 2021)
This paper focuses on investigating the moderating role of business environment on the relationship between FDI and the performance of manufacturing firms in Kenya. Little information is documented on the role of business environment on the relationship between FDI and the performance of firms. The study population comprised of 100 companies registered with KAM as at the time of data collection in 2019, with 10 percent or more foreign ownership. The research used a structured questionnaire to collect primary data. To analyze data, descriptive and inferential statistics was used. The results revealed that there was a statistically significant moderating effect on the relationship between FDI and firm performance. This implies that an incremental change in the interaction between FDI and business environment would generate growth in company’s performance. In Kenya and other SubSahara African countries, the government needs to come up with polices geared towards improving their business environment to spur the growth of the key sectors of the economy.